Решаем:
а) 2x + 3y = 16
3x - 2y = 11
Из 1-го ур-ния y = (16 - 2x) / 3
Подставляем во 2-е
3x - 2*(16 - 2x) / 3 = 11
9x - 32 + 4x = 33
13x = 65, x = 5, y = (16 - 2x) / 3 = 2
ответ: x = 5, y = 2
б) 6(x + y) = 5 - (2x + y)
3x - 2y = -3 (или -3 -3 = -6, уточни)
Из 2-го у = (3х + 3) / 2
6(x + (3х + 3) / 2) = 5 - (2x + (3х + 3) / 2)
6(5x + 3) / 2 = 5 - (7x + 3) / 2
6(5x + 3) = 10 - (7x + 3)
30x + 18 = 10 - 7x - 3
37x = -11, x = -11/37, y = (3х + 3) / 2 = (-33+111) / (2*37) = 78 / (2*37) = 39/37
ответ: x = -11/37, y = 39/37
в) 2x + 3y = 3
5x - 4y = 19
y = (3 - 2x) / 3
5x - 4(3 - 2x) / 3 = 19
15x - 12 + 8x = 57
23x = 69, x = 3
y = (3 - 2x) / 3 = (3 - 6) / 3 = -1
ответ: x = 3, y = -1
г) 3x + 2y = 6
5x + 6y = -2
y = (6 - 3x) / 2
5x + 6(6 - 3x) / 2 = -2
5x + 3(6 - 3x) = -2
5x + 18 - 9x = -2
4x = 20, x = 5
y = (6 - 3x) / 2 = (6 - 15) / 2 = -9/2
ответ: x = 5, y = -4,5
Подробнее - на -
ответ
1) 63/65; 2) -√2/10; 3) √((9+√80)/18); 4) -2√2
1) Косинус разности
cos(a - b) = cos a*cos b + sin a*sin b.
У нас a = arcsin(3/5); sin a = 3/5;
cos a = √(1 - sin^2 a) = √(1 - 9/25) = √(16/25) = 4/5
b = arcsin(5/13); sin b = 5/13;
cos b = √(1 - sin^2 a) = √(1 - 25/169) = √(144/169) = 12/13
sin a = 3/5; sin b = 5/13
Получаем
cos(a - b) = 4/5*12/13 + 3/5*5/13 = 48/65 + 15/65 = 63/65
2) Синус суммы
sin(a + b) = sin a*cos b + cos a*sin b
У нас a = arcctg(1/2); tg a = 1/2;
sin a = √5/5; cos a = 2√5/5.
Проверяем: sin^2 a + cos^2 a = 5/25 + 4*5/25 = 1/5 + 4/5 = 1. Все верно.
Точно также b = arcctg(-1/3); tg b = -1/3;
sin b = √10/10; cos b = -3√10/10
sin^2 b + cos^2 b = 10/100 + 9*10/100 = 1/10 + 9/10 = 1. Все верно.
Получаем
sin(a + b) = √5/5*(-3√10)/10 + 2√5/5*√10/10 = -3√50/50 + 2√50/50 = -√50/50 = -√2/10
3) Косинус половинного угла
cos (a/2) = √((1 + cos a)/2)
У нас a = arcsin(1/9); sin a = 1/9;
cos a = √(1 - sin^2 a) = √(1 - 1/81) = √(80/81) = √80/9
cos (a/2) = √((1 + √80/9)/2) = √((9 + √80)/18)
4) tg a = sin a / cos a
У нас a = arccos(-1/3); cos a = -1/3;
sin a = √(1 - cos^2 a) = √(1 - 1/9) = √(8/9) = √8/3
tg a = (√8/3) / (-1/3) = -√8/3 * 3 = -√8 = -2√2